Toxic waste - Gold, Susan Dudley (New York : Crestwood House, 1990)
Discusses the causes and tragic effects of chemical waste pollution, efforts to reverse existing and prevent future damage, laws regulating the disposal of toxic wastes, and how you can get involved in the fight against pollution.
Includes bibliographical references (p. 43) and index.
Keywords: Hazardous wastes -- Environmental aspects -- Juvenile literature; Hazardous wastes -- Environmental aspects -- United States -- Juvenile literature; Hazardous wastes -- Environmental aspects; Pollution